The effects of perception of video image and online word of mouth on tourists’ travel intentions: Based on the behaviors of short video platform users - Zhou, Yang; Liu, Ligang; Sun, Xiao (Frontiers in Psychology, 2022)
This research discusses the impact of the perception of video images and online word of mouth on tourists’ travel intentions. A survey of 390 users who watched travel videos on short-video platforms was conducted using structural equation modeling. The results are as follows. First, the perception of video images can significantly affect tourists’ intention to visit the destinations. Second, as a mediating variable, online word of mouth can enhance the positive effects of the perception of video images on tourists’ travel intentions. Third, gender had a positive moderating effect, which was particularly obvious in the relationship between the perception of video images and online word of mouth. This research provides a theoretical basis for the utility of tourism-related short videos, which can help stimulate tourists’ intention to visit promoted destinations.